Cross-cultural variation in preference for replantation or revision amputation: Societal and surgeon views. Issue 4 (April 2016) - Maroukis, Brianna L.; Shauver, Melissa J.; Nishizuka, Takanobu; Hirata, Hitoshi; Chung, Kevin C.
Abstract: Treatment decisions after an injury like finger amputation are made based on injury and patient factors. However, decisions can also be influenced by provider and patient preferences. We compared hand surgeon and societal preferences and attitudes regarding finger amputation treatment in Japan and the US. We performed a cross-sectional survey with subjects derived from large tertiary care academic institutions in the US and Japan. We secured 100% participation of American hand surgeon members of the Finger Replantation and Amputation Multicenter Study and presenting hand surgeons at the 32nd Annual meeting of the Central Japanese Society for Surgery of the Hand. Societal preferences were gathered from volunteers at the 2 universities in the US and Japan. There were no significant differences in estimations of function, sensation, or appearance after replantation; American and Japanese societal participants preferred replantation compared to surgeons, although this was more pronounced in Japan. The Japanese society displayed more negative attitudes toward finger amputees than did Japanese surgeons. American respondents anticipated more public stigmatisation of amputees than did American surgeons. Societal preference for replantation was not caused by inflated expectations of outcomes after replantation. Japanese societal preference was likely driven by negative views of finger amputees. American society noted no decrease in physical health after amputation, but did note a quality of life decrease attributed to public stigmatisation. Japanese society and surgeons had a stronger preference for replantation than American society and surgeons, possibly attributed to cultural differences.